Penggunaan Fasilitas WiFi dan Pengaruhnya terhadap Indeks Prestasi Mahasiswa Prodi Pendidikan Matematika (Studi pada Mahasiswa Prodi Pendidikan Matematika STAIN Zawiyah Cot Kala Langsa) - Jelita, Jelita (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2013)
ABSTRACTThe position of information technology is important in all aspects of life. One of the developments that are rapidly from information technology becomes a trending topicPenggunaan Fasilitas Wifi...........Jelita 120is free Wi-Fi. In the world of lectures, students are the biggest consumer that uses Wi-Fi to work on tasks of lectures given by professors. However, the fact that the part of the students, take advantage of free Wi-Fi just to download a task without filtering or examining its contents as well as access to social networks like facebook. Conditions like this is what makes the student being lazy to think more creatively in the task portion. If a student was able to hone his thinking in doing tasks and associated costs by utilizing the free Wi-Fi, then then learning achievements obtained are very satisfactory and boasts. This research aims to know the use of the free Wi-Fi and the influence of the use of facilitiesIf students able to hone his mind in doing theirjobs perkuliahan by utilizing wi-fi, facilities and achievement iearn obtained be very gratifying and plume-. This study aims to know the use of facilities and influence from the use of facilities wi-fi. The facilities to take on duties wi-fi perkuliahan given by a lecturer. But the fact that, obtained part college students use facilities only to wi-fi m gonna download theirjobs without sift or review the content and access as social network facebook.This research uses a quantitative approach with a descriptive method. The population in this research is the entire semester 5 and 7 Mathematics Education Tarbiyah mayor STAIN Zawiyah Cot Kala Langsa 2012-2013 academic year, consisting of 412 people. The research sample is taken as a non-probability as many as 41 people with technical purposive sampling. Data collection techniques in this research is question form and documentation. Data analysis techniques were used to test the hypothesis is variance (Anava) Analysts and test t.Based on the analysis of test of normality on a variable (X) and (Y) variables have normal distributed data with simple linear regression coefficient results indicate Y = 0,452 X 27,075. from the results of the analysis using SPSS anava 20.0 retrieved Fhitung gt; Ftabel (12,517 gt; 4,09), it shows the influence of the use of u201CAda% Wi-Fi against an index of achievement students majoring in mathematics education Prodi Tarbiyah STAIN Zawiyah Cot Kala Langsa% u201D. And test results using SPSS t 20.0, retrieved thitung gt; ttabel (3,538 gt; 1,685). Thus it can be concluded that the use of Wi-Fi facilities significantly influential over student achievement index prodi mathematics education with contributions amounting to 24.3%. Therefore, it is recommended that students use Wi-Fi for things that are useful in particular in completing tasks and associated costs.